2023
DOI: 10.1021/acs.energyfuels.2c03551
|View full text |Cite
|
Sign up to set email alerts
|

Boron–Phosphorus Codoped Coral-like Hard Carbon Anodes for Sodium Ion Storage

Abstract: Hard carbon materials have the advantages of low price, environmental friendliness, and good electrical conductivity but have the disadvantages of unsatisfactory sodium storage capacity and low long-cycle stability. The use of heteroatom doping and structural design can significantly improve the sodium storage properties of carbon materials. In this paper, a boron–phosphorus doped hard carbon material (CABP) was designed by using citric acid as the carbon source. The rich pore structure of CABP also provides f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…In the first cycle, all samples have a cathode peak at about 1 V, which indicates the irreversible decomposition of the electrolyte and the formation of a solid electrolyte interface layer on the carbon surface. Moreover, the cathode peak located close to 0 V and the corresponding anode peak located close to 0.25 V indicate the sodiation/desodiation behavior of sodium ions in the disordered microcrystalline structure of hard carbon . In the subsequent two or three cycles, the CV curves show excellent reversibility.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…In the first cycle, all samples have a cathode peak at about 1 V, which indicates the irreversible decomposition of the electrolyte and the formation of a solid electrolyte interface layer on the carbon surface. Moreover, the cathode peak located close to 0 V and the corresponding anode peak located close to 0.25 V indicate the sodiation/desodiation behavior of sodium ions in the disordered microcrystalline structure of hard carbon . In the subsequent two or three cycles, the CV curves show excellent reversibility.…”
Section: Resultsmentioning
confidence: 89%
“…Moreover, the cathode peak located close to 0 V and the corresponding anode peak located close to 0.25 V indicate the sodiation/ desodiation behavior of sodium ions in the disordered microcrystalline structure of hard carbon. 39 In the subsequent two or three cycles, the CV curves show excellent reversibility. Compared with HC and N-HC, the CV curves of N/S-HC show stronger redox peaks, suggesting higher Na + storage capability, which is consistent with the results of the charge/ discharge test results in Figure 3b−d.…”
Section: Electrochemical Characterizationsmentioning
confidence: 95%
“…Therefore, researchers have also investigated the modulation of the hard carbon materials by multi‐atom doping, and the study showed that the co‐doping of heteroatoms is beneficial to improving the electrochemical performance of hard carbon. Zhang et al [ 100 ] reported a boron‐phosphorus co‐doped hard carbon material with a reversible capacity of 246.8 mAh g −1 at 0.1 A g −1 , and 119.5 mAh g −1 at 10 A g −1 , which proved its excellent rate performance. After 5,000 cycles at a high current of 5 A g −1 , the capacity was still maintained at the level of 161.9 mAh g −1, which is attributed to the synergistic effect synthesized by the elements of phosphorus and boron to add more active sites in the hard carbon structure.…”
Section: Optimization Strategies For Hard Carbonmentioning
confidence: 99%
“…Both the 2-level model and the 3-level model ignored the defect Na, but the defect Na should not be neglected for 2 reasons: on the one hand, the heteroatom defects always appear in HCs, 23 and on the other hand, some experimental studies use heteroatom doping defects to increase the capacity. 30–33…”
Section: Introductionmentioning
confidence: 99%
“…Both the 2-level model and the 3-level model ignored the defect Na, but the defect Na should not be neglected for 2 reasons: on the one hand, the heteroatom defects always appear in HCs, 23 and on the other hand, some experimental studies use heteroatom doping defects to increase the capacity. [30][31][32][33] Moreover, these models investigated the generic case of Na insertion in HCs, while experiments proved that the properties of Na insertion in HCs depends strongly on the specific material properties of HCs. [34][35][36][37] Bommier et al predicted Na capacity based on the pore volume and surface area of HCs; however, the mechanism of Na insertion in HCs is not considered in their study.…”
Section: Introductionmentioning
confidence: 99%